Effector-Triggered Immunity... Controlling Phytophthora through biology of Oomycetes - Tyler, Brett M (Indian Horticulture, 2019)
The causal organisms belonging to Oomycetes cause root, stem, bud and fruit rots, and leaf blights, of nearly all agricultural and horticultural plant species. In India, they cause major diseases on maize (downy mildew), potato (late blight), pearl millet (downy mildew), palm (bud rot), rubber (leaf drop, pod rot and black stripe) and grape (downy mildew). They also cause the most important diseases of a wide variety of tropical fruits and vegetables in India, including citrus, avocado, fig, guava, kiwifruit, mango, chempedek, atemoya, breadfruit, coconut, durian, longan, papaya, pineapple, pond apple, sugar apple, soursop, carambola, rambutan, ginger, gourds and tomato.